Development, validation, and implementation of biomarker testing in cardiovascular medicine state-of-the-art: proceedings of the European Society of Cardiology : Cardiovascular Round Table - Elliott, Perry; Cowie, Martin R; Franke, Jennifer; Ziegler, André; Antoniades, Charalambos; Bax, Jeroen; Bucciarelli-Ducci, Chiara; Flachskampf, Frank A; Hamm, Christian; Jensen, Magnus T; Katus, Hugo; Maisel, Alan; et al. (Cardiovascular research, 2021)
Many biomarkers that could be used to assess ejection fraction, heart failure, or myocardial infarction fail to translate into clinical practice because they lack essential performance characteristics or fail to meet regulatory standards for approval. Despite their potential, new technologies have added to the complexities of successful translation into clinical practice. Biomarker discovery and implementation require a standardized approach that includes: identification of a clinical need; identification of a valid surrogate biomarker; stepwise assay refinement, demonstration of superiority over current standard-of-care; development and understanding of a clinical pathway; and demonstration of real-world performance. Successful biomarkers should improve efficacy or safety of treatment, while being practical at a realistic cost. Everyone involved in cardiovascular healthcare, including researchers, clinicians, and industry partners, are important stakeholders in facilitating the development and implementation of biomarkers. This article provides suggestions for a development pathway for new biomarkers, discusses regulatory issues and challenges, and suggestions for accelerating the pathway to improve patient outcomes. Real-life examples of successful biomarkers—high-sensitivity cardiac troponin, T2* cardiovascular magnetic resonance imaging, and echocardiography—are used to illustrate the value of a standardized development pathway in the translation of concepts into routine clinical practice.